The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/saj2.20460
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of soil aggregate‐associated carbon as influenced by simulated tillage and runoff

Abstract: Tillage practices and water erosion are the most important anthropogenic and natural processes, respectively, driving soil organic C turnover in agricultural land. The aim of this study was to explore the responses of soil organic C (SOC) turnover to tillage and runoff by comparing the variation of soil aggregate-associated organic C (AOC) and intra-aggregate particulate organic C (iPOC) under simulated tillage and runoff conditions. Soil samples were collected from a native vegetation land with no cultivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The inclusion of cover cropping management during the fallow period in soybean monocultures could be an appropriate agricultural management strategy to improve water capture and transport in Mollisols of the Argentinean Pampas region, especially in a Typic Argiudoll. Soil tillage practices and the resulting increase in water erosion is one of the most important anthropogenic processes to drive soil nutrients and SOC turnover in agricultural land. A combination of field study and 30‐d incubation experiment was conducted to explore the responses of surface soil nutrients and SOC turnover to different soil tillage and water erosion patterns in the Mollisol region of Northeast China (Li et al., 2022; Zhao et al., 2022). They found that water erosion played a greater role in controlling the distribution of dissolved OC than tillage erosion, whereas particulate OC distribution was more sensitive to tillage erosion.…”
mentioning
confidence: 99%
“…The inclusion of cover cropping management during the fallow period in soybean monocultures could be an appropriate agricultural management strategy to improve water capture and transport in Mollisols of the Argentinean Pampas region, especially in a Typic Argiudoll. Soil tillage practices and the resulting increase in water erosion is one of the most important anthropogenic processes to drive soil nutrients and SOC turnover in agricultural land. A combination of field study and 30‐d incubation experiment was conducted to explore the responses of surface soil nutrients and SOC turnover to different soil tillage and water erosion patterns in the Mollisol region of Northeast China (Li et al., 2022; Zhao et al., 2022). They found that water erosion played a greater role in controlling the distribution of dissolved OC than tillage erosion, whereas particulate OC distribution was more sensitive to tillage erosion.…”
mentioning
confidence: 99%